Membrane-tethered metalloproteinase expressed by vascular smooth muscle cells limits the progression of proliferative atherosclerotic lesions - Barnes, RH (Ovid Technologies (Wolters Kluwer Health), 2019)
10.1161/JAHA.116.003693